Évolution des modèles d’implantation de la villégiature sur le littoral tunisois - Sondès Zaier; Hichem Rejeb; Pierre Donadieu (Projets de Paysage)
The transformation of the coasts of the region of Tunis into an attractive shoreline, with a few holiday resorts, is the result of particular socio-cultural and economic conditions and circumstances. Changes in both perceptions and mentalities, needed to build these places of leisure activities, took place gradually in selected and privileged sites during the period between the first half of the eighteenth century and the late nineteenth century. Within less than a century, highly coveted seaside resorts have been developed associated with a new passion for sea bathing and beach activities. This enthusiasm was illustrated in Tunisia by the construction of many recreational palaces and summer residences. These new settlements, built according to a step-by-step process, have generated several urban models transforming an abandoned area to an authentic touristic and resort destination for the upper middle classes as well as a popular place for summer leisure.